Transmisión OFDM por canales acústicos subacuáticos. - Gonzalez-Monge, María del Castillo; Cobacho Ruiz, Pablo; Fernández-Plazaola, Unai; Martos-Naya, Eduardo (My University, 2024)
This paper presents a multicarrier modulation sys tem with low complexity designed for wide-band underwater acoustic communications within the ultrasonic range (from 32 kHz to 128 kHz). Underwater Acoustic Communications (UAC) systems are recognized as one of the most challenging communication media in use today due to their temporal and frequency selectivity characteristics. This paper addresses the development of an OFDM (Orthogonal Frequency Division Multiplexing) system employing QPSK (Quadrature Phase Shift Keying) modulation. Paper describes the performance com parison between two methods of channel response estimation using pilots: time interpolation versus frequency interpolation. The system’s performance is evaluated using impulse responses obtained from shallow water measurements conducted in the Mediterranean Sea.
Keywords: Multiplexación; Telecomunicaciones; Transductores ultrasónicos; QPSK; UAC; OFDM